Analisis Tingkat Kepuasan Pengguna Jasa Terhadap Kualitas Kinerja Pelayanan Terminal Bus Anjuk Ladang, Nganjuk - Prasetiyo, Ahmad Rendra; Saves, Faradlillah; Mawariza, Putri Suci (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
The bus terminal is a vital component in the transportation infrastructure system which plays an important role in supporting smooth passenger transportation. The Anjuk Ladang Terminal in Nganjuk Regency, as a type B terminal, has a strategic function in serving community mobility between cities within the province, city transportation and rural transportation. Based on field observations, several problems were found, such as limited waiting space, lack of cleanliness, and the presence of an inadequate bus fleet. This research aims to analyze the level of user satisfaction with the quality of service provided by the Anjuk Ladang Terminal. The method used is Importance Performance Analysis (IPA), which allows identifying service aspects that need to be improved. The research results show that the average satisfaction level of Anjuk Ladang Terminal service users reaches 93%. This percentage indicates that the majority of passengers are satisfied with the terminal's service performance, and that the terminal has succeeded in meeting or exceeding user expectations in terms of services and facilities available.